Ankyloglossia: Update on Trends in Diagnosis and Management in the United States, 2012‐2016. (19th May 2020) - Wei, Eric X.; Tunkel, David; Boss, Emily; Walsh, Jonathan
Abstract : Ankyloglossia, or "tongue‐tie, " refers to limited tongue mobility caused by a restrictive lingual frenulum. Previous studies have demonstrated rapid increases in diagnosis and treatment of ankyloglossia in the United States up to 2012. We performed an updated retrospective review of data from the National Inpatient Sample (NIS), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality (AHRQ) to evaluate trends in diagnosis of ankyloglossia and use of lingual frenotomy in the hospital setting. From 2012 to 2016, there was an 110.4% increase in reported diagnosis of ankyloglossia in the inpatient setting with similar increases in lingual frenotomy procedures. As seen previously, sex, type of insurance, median income ZIP code, and geographic region were associated with diagnosis of ankyloglossia. The observed trends from prior to 2012 have continued to increase, while unanswered questions about diagnostic criteria and about which infants should undergo frenotomy remain.